Analysis of factors affecting sharia compliance levels in sharia banks in Indonesia - Fajar Satriya Segarawasesa (Asian Journal of Islamic Management (AJIM), 2021)
Purpose: This study aims to analyze the factors that influence the level of sharia compliance in sharia banks in Indonesia. In particular, this study examines the effect of liquidity, firm size, Sharia Supervisory Board Size, and Audit Committee on the level of sharia compliance in sharia banks in Indonesia.Methodology: This study uses quantitative methods with secondary data in the form of sharia bank annual reports 2014-2018. The data analysis uses regression test with the help of SPSS software.Findings: The results of the analysis show that the size of the sharia supervisory board and audit committee has a positive effect on the level of sharia compliance. The findings of this study contribute to the literature on sharia compliance and disclosure in Sharia banking in Indonesia.Practical implications: This research also has implications for sharia banking, especially in Indonesia, as an evaluation material in improving the quality of financial reports.Originality: This study uses the sharia compliance index as a measuring tool for the level of compliance of sharia banks which is rarely used by previous studies.